PENGARUH PENERAPAN TEORI BELAJAR HUMANISTIK TERHADAP HASIL BELAJAR MAHASISWA PADA MATA KULIAH KEWIRAUSAHAAN - Aradea, Riswan; Harapan, Edi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2019)
The problem in this study was the lack of attention of students to the material delivered by the lecturers so that there are still many student grades under mastery. The independent variable (X) the use of the application of humanistic learning theory and dependent variable (Y) learning outcomes. The results of data analysis obtained from a simple linear regression equation, Y = 67.64 + 15.94X, it can be stated that there is an influence of the application of humanistic learning theory on student learning outcomes in entrepreneurship courses and the results of hypothesis testing expressed by the test "t" is tcount = 8,48> ttable = 1,992. the magnitude of the effect is 45%, while the level of the relationship of variables (free) to the application of humanistic learning theory to the variable (bound) learning outcomes with the magnitude of the effect is 0.67 (in sufficient categories)